Discrimination against gay and transgender people in Latin America: A correspondence study in the rental housing market - Nicolás Abbate; Inés Berniell; Joaquín Coleff; Luis Laguinge; Margarita Machelett; Mariana Marchionni; Julián Pedrazzi; María Florencia Pinto (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2022)
We assess the extent of discrimination against gay and transgender individuals in the rental housing markets of four Latin American countries. We conducted a large-scale field experiment building on the correspondence study methodology to examine interactions between property managers and fictitious couples engaged in searches in a major online rental housing platform. We find evidence of discriminatory behavior against heterosexual couples where the female partner is a transgender women (trans couples): they receive 19% fewer responses, 27% fewer positive responses, and 23% fewer invitations to showings than heterosexual couples. However, we find no evidence of discrimination against gay male couples. We also assess whether the evidence is consistent with taste-based discrimination or statistical discrimination models by comparing response rates when couples signal a high socioeconomic status (high SES). While we find no significant effect of the signal on call-back rates or the type of response for high-SES heterosexual or gay male couples, trans couples benefit when they signal a high SES. Their call-back, positive-response, and invitation rates increase by 25%, 36% and 29%, respectively. These results suggest the presence of discrimination against trans couples in the Latin American online rental housing market, which seems consistent with statistical discrimination. Moreover, we find no evidence of heterosexual couples being favoured over gay male couples, nor evidence of statistical discrimination for gay male or heterosexual couples.
Keywords: C93; J15; R23; R3; 330; LGBTQ+; Discrimination; Correspondence study; Rental housing market; LatinAmerica